1998
DOI: 10.1023/a:1022294028903
|View full text |Cite
|
Sign up to set email alerts
|

Fertile Ground for Community: Inner‐City Neighborhood Common Spaces

Abstract: Research suggests that the formation of neighborhood social ties (NSTs) may substantially depend on the informal social contact which occurs in neighbor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
271
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(318 citation statements)
references
References 57 publications
11
271
0
10
Order By: Relevance
“…92 Green spaces may also affect health by providing spaces for interaction and shared interest, thereby promoting social capital and cohesion. [93][94][95][96] Density of urban tree canopy has been found to be a predictor of social capital. 96 In a public housing setting in Chicago, residents living in areas with green common space reported more use of common space and more social cohesion compared to those living in a barren, ungreen areas.…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…92 Green spaces may also affect health by providing spaces for interaction and shared interest, thereby promoting social capital and cohesion. [93][94][95][96] Density of urban tree canopy has been found to be a predictor of social capital. 96 In a public housing setting in Chicago, residents living in areas with green common space reported more use of common space and more social cohesion compared to those living in a barren, ungreen areas.…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%
“…96 In a public housing setting in Chicago, residents living in areas with green common space reported more use of common space and more social cohesion compared to those living in a barren, ungreen areas. 93 …”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have observed associations between community gardening and health [1][2][3][4][5][6][7][8], social [6,9], and economic benefits [6,7,10], and gardening in general has been associated with cardiovascular [11,12] and mental [13][14][15] health benefits. Historically, backyard and community gardens have made substantial contributions to the food supply; World War II ''Victory Gardens'' have been credited with providing an estimated 40% of the U.S. vegetable supply [16].…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers have noted the particular benefits of community gardening and greening initiatives in lower SES communities (Faber-Taylor, Wiley, Kuo, Bacaicoa, & Sullivan, 1998;Kuo & Sullivan, 2001;Kuo, Sullivan, Coley, & Brunson, 1998;Trust for Public Land, 1995), little is understood about the relationship between school ground greening and SES. Of course the consequences of different SES's manifest themselves in numerous ways beyond the most obvious issue of funding and extend into other aspects of greening projects such as access to adult assistance as well as perceptions of the importance of green school grounds.…”
Section: Introductionmentioning
confidence: 99%